Commercial hospitality in Amazon Context/Belém - PA (Research, Society and Development, 2022)
The study deals with the customer experience regarding the level of satisfaction in the regional Amazonian hospitality, in the city of Belém do Pará. It aims to create a satisfaction index to the guest and offer theoretical and practical contributions to the user experience in regional commercial hospitality (CH). The methodology includes data collection from guests and commercial accommodation, from the Metropolitan Region of Belém (RMB). The data were subjected to exploratory factor analysis applied to the cluster analysis technique to create satisfaction groups. The study indicates equality between men and women, although schooling at the secondary level of education, presents a difference in relation to the other levels. On the other hand, the group between 31 and 50 years old presents a good level of satisfaction at the CH. It is concluded that there are guests in general satisfied with the experience in the commercial hospitality of Belém do Pará. The investigation expands the theoretical knowledge about the perception of the guest in the commercial hospitality. In practice, it suggests the realignment of strategic planning to the MHCs in the Metropolitan Region of Belém.